2019
DOI: 10.1093/gji/ggz310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of geomagnetic secular variation for the last 1.5 Ma recorded by volcanic rocks of the Trans Mexican Volcanic Belt: new data from Sierra de Chichinautzin, Mexico

Abstract: Summary The great wealth of volcanism along the Trans Mexican Volcanic Belt (TMVB) and the need to improve the secular variation curve of the Earth magnetic field of the region is the aim of this research. 300 oriented cores from 33 sites and 21 individual cooling units were acquired from Sierra de Chichinautzin volcanic field (ChVF) and Sierra de Santa Catarina (SSC). Directional analysis and rock magnetic experiments were performed (e.g. thermal demagnetization, hysteresis loop, susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In Mexico, a large number of archaeomagnetic studies on baked clays or lava flows have been published in the last 10 years (e.g., Fanjat et al, 2013;Mahgoub et al, 2017;Mahgoub et al, 2019bMahgoub et al, , 2019aMahgoub et al, 2019aMahgoub et al, , 2019bPétronille et al, 2012;Rodriguez-Ceja et al, 2009;Rodriguez-Trejo et al, 2019;Terán et al, 2016), but a recent critical analysis of the Mexican dataset showed that around 70% of these data cannot be considered as high quality, according to basic selection criteria. Two local secular variation curves have been recently proposed using only Mexican data (Mahgoub et al, 2019a) or also some from the southwestern United States (Goguitchaichvili et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, a large number of archaeomagnetic studies on baked clays or lava flows have been published in the last 10 years (e.g., Fanjat et al, 2013;Mahgoub et al, 2017;Mahgoub et al, 2019bMahgoub et al, , 2019aMahgoub et al, 2019aMahgoub et al, , 2019bPétronille et al, 2012;Rodriguez-Ceja et al, 2009;Rodriguez-Trejo et al, 2019;Terán et al, 2016), but a recent critical analysis of the Mexican dataset showed that around 70% of these data cannot be considered as high quality, according to basic selection criteria. Two local secular variation curves have been recently proposed using only Mexican data (Mahgoub et al, 2019a) or also some from the southwestern United States (Goguitchaichvili et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a long tradition of archeomagnetic studies in Northern and Central America, with the first studies in the mid 60s (e.g., Bucha et al, 1970;Lee, 1975 for Mexico and see Jones et al, 2021 for USA) and continuous improvements since (e.g., Alva-Valdivia et al, 2020Dubois, 1989;Hagstrum & Champion, 2002;Hervé, Perrin, Alva-Valdivia, Tchibinda Madingou, et al, 2019;Jones et al, 2020Jones et al, , 2021Lengyel & Eighmy, 2002;Mahgoub, Juárez-Arriaga, Böhnel, Manzanilla, & Cyphers, 2019;Morales et al, 2009;Pétronille et al, 2012;Rodríguez-Trejo et al, 2019;Schaafsma et al, 2002;Soler-Arechalde et al, 2019;Sternberg, 1989;Wolfman, 1990). For the past 2 kyrs, around 325 intensities and 690 directions, respectively 11% and 12% of the worldwide archeomagnetic data set (GEOMAGIA50.v3.4; Brown et al, 2021), have been published.…”
mentioning
confidence: 99%